2012
DOI: 10.1159/000345742
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Safety and Efficacy of a First-Line Treatment with Modified FOLFOX-4 in Unresectable Advanced or Recurrent Gastric Cancer Patients

Abstract: Aim: Dismal clinical results in patients with unresectable advanced or recurrent gastric cancer highlight the need for effective systemic chemotherapy. An increase in adverse events associated with systemic chemotherapy is shown in elderly patients, but it remains controversial whether they should receive the same chemotherapy used for younger patients. We retrospectively studied 73 patients with unresectable advanced or recurrent gastric cancer, including 48 nonelderly patients (<65 years old) and 25 elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The most common grade 3-4 toxicity was neutropenia (41%) in that trial wheras 9,1 and 16,7 in ECF and DCF group respectively in our study (Louro et al, 2013). Yeh et al showed that FOLFOX has 11,2 months median OS in first line setting in advanced or recurrent gastric cancer (Yeh et al, 2012). The result of our study was correlated with literature.…”
Section: Discussionsupporting
confidence: 87%
“…The most common grade 3-4 toxicity was neutropenia (41%) in that trial wheras 9,1 and 16,7 in ECF and DCF group respectively in our study (Louro et al, 2013). Yeh et al showed that FOLFOX has 11,2 months median OS in first line setting in advanced or recurrent gastric cancer (Yeh et al, 2012). The result of our study was correlated with literature.…”
Section: Discussionsupporting
confidence: 87%
“…In numerous phase II studies, combination chemotherapy with 5-FU, folinic acid (leucovorin; LV) and oxaliplatin (FOLFOX regimens), has exhibited considerable antitumor activity and a tolerable toxicity profile in AGC patients using different doses and schedules (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In a study analyzing 643 patients enrolled in 5 separate chemotherapy trials by the Japanese Clinical Oncology Group, the 5-year survival for patients with metastasis confined to the liver and treated with systemic therapy alone was 1.7% [17]. Palliative chemotherapy using various regimens has been widely used as a treatment of choice, but only modest improvements in overall survival have been observed, with the median survival increasing from approximately 3 months to 7-15 months; long-term survival is rarely reported [18,19]. In particular considering the few trials evaluating systemic chemotherapy in the subset of patients with liver-only metastatic involvement, the 5-year survival rates do not reach 2% [20].…”
Section: Discussionmentioning
confidence: 99%